Behaviour of RC beams with recycle aggregate as coarse aggregate replacement with addition of steel fibres - Mohamad Badrul Hisyam, Mohd Yusoff (2017)
Sustainability is a pressing concern on the 21st century. Social development in most countries is raising awareness of the needs of future generations and legislations to protect the present and future quality of life. One of the major challenge in developing nations that due to its ever increasing quantities is construction and demolition waste disposal. So, the purpose of this study are to determine the behaviour of reinforced concrete beams that are constructed from normal aggregates (NA) and recycled concrete aggregates (RCA), and to investigate the performance of addition of steel fibres in recycled reinforced concrete beams. Recycled aggregates were made by crushing the waste concrete of laboratory test cubes and beams. There are four types of concrete mixtures that will be tested; [1] Control Mixture (NC), [2] 50% Recycled Concrete Aggregate (RCA) Mixture, [3] 50% Recycled Concrete Aggregate (RCA) + 1.0% Steel Fibres Mixture (RCA-SF1%), [4] 50% Recycled Concrete Aggregate (RCA) + 2.0% Steel Fibres Mixture (RCA-SF2%). The purpose of adding steel fibres inside concrete mixture as to control the crack development, increases the ultimate shear strength, decreasing the deflection of concrete beams, thus, and also enhancing aggregate interlock with cement inside concrete mixture. As conclusion, this study outcome suggests that the promising enhancement of load carrying capacity, controlled cracking pattern and also failure mode of the reinforced concrete beams.